2011
DOI: 10.4314/ajid.v5i1.66506
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of auditory manifestations in a group of adult with AIDS prior to antiretroviral therapy

Abstract: The chief objective of the current study was to investigate the auditory status in a group of adults with AIDS before commencing antiretroviral therapy (ART) in a hospital outpatient clinic in Gauteng, South Africa. A total sample of 150 participants, aged between 20 and 46 years, was assessed following a prospective qualitative research design. All participants underwent case history interviews and medical record reviews, otoscopy and tympanometry, as well as conventional pure tone audiometry testing. Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 34 publications
6
30
0
Order By: Relevance
“…These findings are consistent with those studies from high‐income countries . In children, the conductive hearing loss is likely to result from frequent ear infections; several studies reported frequent CSOM among the children with HIV . Although the study samples were generally small, these CSOM prevalences were similar to the otoscopical abnormalities found in 14–37% of ears in high‐income countries .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with those studies from high‐income countries . In children, the conductive hearing loss is likely to result from frequent ear infections; several studies reported frequent CSOM among the children with HIV . Although the study samples were generally small, these CSOM prevalences were similar to the otoscopical abnormalities found in 14–37% of ears in high‐income countries .…”
Section: Discussionsupporting
confidence: 90%
“…The characteristics of the eligible studies are summarised in Table . Eleven studies focused on children, nine on adults and one on people of all ages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, investigators studied the ototoxicity of ARV drugs and HIV. 7,13,14 They confirmed the abovementioned findings and emphasized the need for closer monitoring of hearing in patients with HIV undergoing HAART. 13 Since May 2007 in Cameroon, HAART has been available free of charge nationwide.…”
supporting
confidence: 74%
“…To date, we have no explanation for this left-sided predominance, which was also found by Khoza-Shangase. 14 In fact, ototoxicity can also lead to unilateral hearing loss. 23 As for the severity of hearing loss, 42…”
Section: Discussionmentioning
confidence: 99%